2015
DOI: 10.4103/2231-0770.165126
|View full text |Cite
|
Sign up to set email alerts
|

English language proficiency and academic performance: A study of a medical preparatory year program in Saudi Arabia

Abstract: Introduction:All medical schools in Saudi Arabia have English as the primary official medium of instruction. Most of the high school education, however, is delivered in Arabic and hence the transition to an English based learning environment tends to be difficult for some students. Our study aims to correlate English language proficiency with academic performance among medical students in their preparatory year.Methods:A cross-sectional study design was used. Test scores of 103 preparatory year students (54 fe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
27
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(38 citation statements)
references
References 6 publications
5
27
1
Order By: Relevance
“…[20] The proficiency of the students in the use of the English language is a critical determinant in understanding not only Nursing Leadership and Management concepts but also other subjects or courses in the nursing program. [21] Nursing being one of the healthcare professions requires the mastery of English as a language of communication among colleagues in the continuity of care. [22] Grades obtained in a particular course may impact future performance.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[20] The proficiency of the students in the use of the English language is a critical determinant in understanding not only Nursing Leadership and Management concepts but also other subjects or courses in the nursing program. [21] Nursing being one of the healthcare professions requires the mastery of English as a language of communication among colleagues in the continuity of care. [22] Grades obtained in a particular course may impact future performance.…”
Section: Discussionmentioning
confidence: 99%
“…[14] The NPVS-R questionnaire consists of 26 items, which are divided into the five factors previously mentioned. Items 16,17,18,20,21,22,23,24, and 25 are classified under factor 1, which is caring; items 4, 10, 11, 19, and 26 are classified under factor 2, which is activism; items 1, 2, 9, 14, and 15 are classified under factor 3, which is trust; items 6, 7, 5, and 8 are classified under factor 4, which is professionalism; and lastly, items 3, 12, and 13 are classified under factor 5, which is justice. Responses are rated on a scale ranging from 1 ("not important") to 5 ("most important") with a possible range of scores between 26 and 130.…”
Section: Instrumentmentioning
confidence: 99%
“…Kong et al (2012) suggested students are more prepared for meaningful instruction and performance in academic subjects that are taught using the English language if they are proficient in English. There are suggestions that students who are not English native but fluent in English would perform better in higher education compared to students who are not (Kaliyadan et al, 2015;Martirosyan et al, 2015).…”
Section: English Language Proficiency and Students' Performancementioning
confidence: 99%
“…Addition of this strategy will have a positive effect on the students' vocabulary. (Kaliyadan et al, 2015). It is a planned oral reading of a text connected to the topic of a study.…”
Section: Muhammad Khalid Mehmood Sajid Abdullah Al Fraidan mentioning
confidence: 99%